Association between early sexual initiation and sexually transmitted infections among Peruvian reproductive-age women - Jhosuny Perez-Fernandez; Diego O. Arroyo-Velasco; Mariella R. Huaman; Sarai G. Chavez-Bustamante; Anita P. Llamo-Vilcherrez; Carolina J. Delgado-Flores; Carlos J. Toro-Huamanchumo; Carlos J. Toro-Huamanchumo (Frontiers Media S.A., 2023)
BackgroundSexually transmitted infections (STIs) are a serious public health problem worldwide, especially among reproductive-age women. The early sexual onset of sexual intercourse (EOSI) has been suggested as a risk factor, although there is no data at the national level.ObjectiveTo evaluate the association between EOSI and STIs in Peruvian women of childbearing age.MethodsAnalytical cross-sectional study with secondary data analyzes of the Peruvian Demographic and Family Health Survey 2018. The outcome was the presence of STIs in the last 12 months and the exposure variable was EOSI (age < 15 years at the time of their first sexual experience). To evaluate the association of interest, crude and adjusted prevalence ratios (aPRs) were calculated using generalized linear models with Poisson family and logarithmic link function.ResultsWe analyzed data from 31,028 women of childbearing age. The 11.3% reported having STIs in the last 12 months and 20.2% of the participants had an EOSI. After adjusting for potential confounders, we found that EOSI was associated with STIs (aPR: 1.27; 95% CI: 1.08-1.50; p = 0.005). When conducting stratified analysis by area of residence and number of sexual partners, this association was maintained in women living in urban areas (aPR: 1.36; 95% CI: 1.11-1.66; p = 0.003) those who did not report having a history of multiple sexual partners (aPR: 1.27; 95% CI: 1.08-1.51; p = 0.005), and those in the middle (aPR: 1.42; 95% CI: 1.03-1.97; p = 0.034) and highest (aPR: 2.12; 95% CI: 1.33-3.39; p = 0.002) wealth quintiles.ConclusionAmong reproductive-age women from Peru, EOSI was associated with STIs, especially in women living in urban areas, with no history of multiple sexual partners, and belonging to the middle to higher wealth index. The implementation of measures to prevent EOSI and fostering appropriate sexual health counseling for women with EOSI is advised.